A new approach in deactivation analysis: effects of coke loading on diffusivity and acidic properties - Songip, Ahmad Rahman; Akiyama, Takashi; Masuda, Takao; Hashimoto, Kenji (1995)
The objective of this study is to correlate the coke amount and acidic properties of the coked catalyst to the rate constants. This paper also propose a method to predict diffusivity coefficients or large hydrocarbon compounds on coked catalysts. The reaction system was the catalytic cracking of heavy oil from waste plastics over REY zeolite catalysts. The detail experimental work and results are available in full text article.